RELIABILITY ANALYSIS OF PWR REACTOR PROTECTION SYSTEM - Kowal, Karol; Borysiewicz, Mieczysław (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
The aim of this work was to assess the probability of the Westinghouse PWR reactor protection system (RPS) unavailability. The reference facility for which the analysis has been made was Surry Nuclear Power Plant located in the United States. This work includes RPS fault tree development and qualitative analysis using the SAPHIRE code, as well as the uncertainty assessment by applying the Monte Carlo techniques.